2008
DOI: 10.1159/000151744
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Sirt1 Decreases Adipocyte Formation during Osteoblast Differentiation of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSC) can differentiate into osteoblasts, adipocytes, chondrocytes and myoblasts. It has been suggested that a reciprocal relationship exists between the differentiation of MSC into osteoblasts and adipocytes. Peroxisome proliferator-activated receptor γ2 (PPARγ2) is a key element for the differentiation into adipocytes. Activation of the nuclear protein deacetylase Sirt1 has recently been shown to decrease adipocyte development from preadipocytes via inhibition of PPARγ2. In vitro, MSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 20 publications
(13 reference statements)
7
86
0
Order By: Relevance
“…Interestingly, MSC derived from SIRT1 knock-out mice showed clearly reduced chondrogenic potential in vitro (67). Indeed, these results are consistent with earlier reports demonstrating that SIRT1 is able to interact with other transcription factors, like Runx2 in osteoblasts or scleraxis in tenocytes (38,62,68) or p53, NF-B, myogenic differentiation, high mobility group I, E2F transcription factor, peroxisome proliferator-activated receptor-␥, and forkhead box O (27,28,30,69).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, MSC derived from SIRT1 knock-out mice showed clearly reduced chondrogenic potential in vitro (67). Indeed, these results are consistent with earlier reports demonstrating that SIRT1 is able to interact with other transcription factors, like Runx2 in osteoblasts or scleraxis in tenocytes (38,62,68) or p53, NF-B, myogenic differentiation, high mobility group I, E2F transcription factor, peroxisome proliferator-activated receptor-␥, and forkhead box O (27,28,30,69).…”
Section: Discussionsupporting
confidence: 90%
“…(c) ENPP1, known to be the gene for insulin resistance/type 2 diabetes, hyperglycemia, and obesity (Meyre et al 2005), was recently shown by us and others to be associated with osteoporosisrelated traits (Cheung et al 2010). (d) Activation of the nuclear protein deacetylase Sirt1 (an antioxidant protein involved in aging) has recently been shown to decrease adipocyte development from preadipocytes, therefore promoting differentiation of mesenchymal stem cells into osteoblasts via inhibition of PPARγ (Backesjo et al 2009). (e) Loss of the carboxyl terminus of Hsp70-interacting protein (CHIP or STUB1), a ubiquitin ligase co-chaperone, is associated with reduced longevity and accelerated aging, including atrophy of skeletal muscle, low BMD, and severe kyphosis in mice (Min et al 2008).…”
Section: Pleiotropymentioning
confidence: 99%
“…Known to be important in linking organism aging and metabolism, SIRT1 is a type of histone deacetylase that also can interact and modulate the actions of transcription factors through its deacetylase activity [57]. We have very recently found that replicative senescence of fetal MSCs is associated with decreased expression of SIRT1 [13] and SIRT1 has also been reported to affect lineage commitment in MSCs [58,59]. In this study, however, we did not find SIRT1 levels differ between adult BM and hDE-MSCs (Fig.…”
Section: Discussionmentioning
confidence: 99%